The Influence of Village Fund Management on Rural Development in Kotawaringin Barat Regency - Hanantajaya, Adhe Repsi; Pratomo, Devanto Shasta (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study examines the influence of Village Fund (DD) and Village Fund Allocation (ADD) absorption on the Village Development Index (IDM) across 81 villages in Kotawaringin Barat Regency during the 2019–2023 period. Employing a panel data regression model with a time-lag structure of one to three years, the results indicate that DD absorption significantly contributes to IDM improvement, particularly within two to three years after fund disbursement. These findings highlight the presence of a lag effect in village development driven by decentralized funding. The results underscore the importance of medium-term development planning and continuous program evaluation to enhance policy effectiveness at the village level.